Stigma, facility constraints, and personal disbelief: why women disengage from HIV care during and after pregnancy in Morogoro Region, Tanzania - McMahon-Rössle, Shannon A. (Aids and behavior, 2017)
Millions of children are living with HIV in sub-Saharan Africa, and the primary mode of these childhood infections is mother-to-child transmission. While existing interventions can virtually eliminate such transmission, in low- and middle-income settings, only 63 % of pregnant women living with HIV accessed medicines necessary to prevent transmission. In Tanzania, HIV prevalence among pregnant women is 3.2 %. Understanding why HIV-positive women disengage from care during and after pregnancy can inform efforts to reduce the impact of HIV on mothers and young children. Informed by the tenets of Grounded Theory, we conducted qualitative interviews with 40 seropositive postpartum women who had disengaged from care to prevent mother-to-child transmission (PMTCT). Nearly all women described antiretroviral treatment (ART) as ultimately beneficial but effectively inaccessible given concerns related to stigma. Many women also described how their feelings of health and vitality coupled with concerns about side effects underscored a desire to forgo ART until they deemed it immediately necessary. Relatively fewer women described not knowing or forgetting that they needed to continue their treatment regimens. We present a theory of PMTCT disengagement outlining primary and ancillary barriers. This study is among the first to examine disengagement by interviewing women who had actually discontinued care. We urge that a combination of intervention approaches such as mother-to-mother support groups, electronic medical records with same-day tracing, task shifting, and mobile technology be adapted, implemented, and evaluated within the Tanzanian setting.
Gesehen am 20.11.2018
First online 17 August 2016